OPTIMISASI PORTOFOLIO UNTUK GREEN ECONOMY MENGGUNAKAN METODE SHARPE RATIO, TREYNOR RATIO, DAN JENSEN ALPHA - Werry Febrianti; Ainol Yaqin (MATHunesa: Jurnal Ilmiah Matematika, 2025)
Investment strategies based on Environmental, Social, and Governance (ESG) principles are gaining popularity as a response to global sustainability challenges. This study evaluates the performance of an ESG-based stock portfolio derived from the IDX ESG Leaders index, representing a green investment strategy in the Indonesian market. Five constituent stocks—BBCA, UNVR, TLKM, SMGR, and DSNG—were selected based on ESG risk ratings and market capitalization. Using daily return data from January 2021 to April 2025, the portfolio performance was assessed through Sharpe Ratio, Treynor Ratio, and Jensen Alpha. The results show that BBCA demonstrated the highest risk-adjusted efficiency with a Sharpe Ratio of 0.00445, while DSNG showed the strongest performance relative to market expectations with a positive Jensen Alpha of 0.000003. TLKM recorded the highest Treynor Ratio at 0.00057. These findings suggest that ESG-oriented stock selection, when combined with rigorous risk-return analysis, can support the development of competitive and sustainable portfolios. This study highlights the financial viability of green investing and its potential contribution to sustainable capital markets.